A coupled spectrophotometric enzyme assay for the determination of pectin methylesterase activity and its inhibition by proteinaceous inhibitors - Grsic-Rausch, Slobodanka; Rausch, Thomas (Analytical biochemistry, 2004)
Pectin methylesterase (PME; EC 3.1.1.11) activities are widespread in bacteria, fungi, and plants. PME-mediated changes in cell wall pectin structure play important roles in plant development. Genome sequencing projects have revealed the existence of large PME multigene families in higher plants. Additional complexity for PME regulation arises from the presence of specific PME inhibitor proteins (PMEI) in plant cells. Several assay procedures for the determination of PME activity have been reported. However, previous protocols suffered from various limitations. Here we report a protocol for a coupled enzyme assay based on methanol oxidation via alcohol oxidase (AO; EC 1.1.3.13) and subsequent oxidation of formaldehyde by formaldehyde dehydrogenase (FDH; EC 1.2.1.3). This simple and robust assay allows the continuous monitoring of PME activity in the neutral pH range. Furthermore, as plant PMEIs do not interfer with AO and FDH activities, this assay is suitable for the characterization of the inhibition kinetics of PMEI.